Photoelectric-Fenton catalyst and preparation method and application thereof
By loading TiO2 nanowires and Fe3O4 quantum dot modified carbon nitride materials on the graphite felt substrate, an efficient photoelectric-Fenton catalyst was formed, which solved the problems of low efficiency and high cost of antibiotic-contaminated water treatment in the prior art, and achieved efficient, stable and economical degradation effects.
Patent Information
- Application Number
- CN202411821571.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-04
AI Technical Summary
Existing photocatalytic technology and Fenton technology have problems of low efficiency, high cost and poor material stability when dealing with antibiotic-contaminated water. In particular, the bandwidth gap width and surface area of titanium oxide and graphite phase carbon nitride materials limit their application.
Carbon nitride material with a graphite felt as a conductive substrate, loaded with TiO2 nanowires and Fe3O4 quantum dot modification, was used to grow TiO2 nanowires by hydrothermal method, and Fe3O4/CN was loaded onto the graphite felt by electrophoretic deposition to form an efficient photoelectric-Fenton catalyst.
It has achieved efficient degradation of antibiotic pollutants, with high degradation efficiency, strong universality, superior stability, and simple preparation method and low cost.
Smart Images

Figure CN119746905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photoelectrocatalysis technology, and more specifically, to a photoelectrocatalyst and a preparation method and application thereof. Background Art
[0002] As a typical pollutant, antibiotics can enter the water environment through various pathways. They are constantly enriched in the environment, which not only induces genetic resistance mutations, but also has the possibility of synergistic pollution with heavy metals, posing a threat and damage to the ecosystem, which has attracted the attention of scholars. Therefore, it is very necessary to find an energy-saving and efficient sewage treatment technology to remove antibiotic pollutants in water bodies.
[0003] In the past few decades, the traditional technologies for treating antibiotic wastewater include physical adsorption, biodegradation, advanced oxidation processes (AOPs), etc. Among them, AOPs is the most widely used technology with good degradation effect and the most promising development prospects. Common methods of AOPs include photocatalytic technology, Fenton technology, and electrochemical oxidation technology. These methods can oxidize and decompose antibiotic pollutants in water into non-toxic and harmless small molecules such as CO2 and H2O, and have a certain degradation effect on the treatment of antibiotic wastewater. However, a single method has its limitations.
[0004] Titanium oxide (TiO2) is an excellent n-type semiconductor functional material with good chemical stability, non-toxicity, corrosion resistance, antibacterial, strong UV absorption, high catalytic efficiency, low preparation cost, etc. However, TiO2 has a wide bandgap and can only absorb ultraviolet light below 387.5nm. Its low quantum efficiency and other disadvantages limit its application.
[0005] Graphitic carbon nitride (g-C3N4) has set off a research boom in the field of photocatalysis due to its attractive electronic band structure and band position, high physicochemical stability and "earth-abundant" properties, as well as its suitable and excellent chemical stability, environmental affinity, reliable chemical inertness, low toxicity, low cost, and easy synthesis. However, traditional g-C3N4 has disadvantages such as low visible light utilization efficiency and rapid charge carrier recombination due to its limited surface area. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a photoelectric-Fenton catalyst and a preparation method and application thereof. The catalyst of the present invention is a graphite felt as a conductive substrate and TiO2 nanowires and Fe3O4 quantum dots modified carbon nitride loaded on the conductive substrate, and is equipped with a preparation method matching the components, so that the obtained catalyst has high degradation efficiency, strong universality, excellent stability, can be used to degrade emerging pollutants, and the preparation method is simple and low cost.
[0007] To achieve the above object, the technical solution of the present invention is as follows:
[0008] A photoelectric-Fenton catalyst, which consists of a conductive substrate, TiO2 nanowires and Fe3O4 quantum dot modified carbon nitride; wherein the conductive substrate is graphite felt, and the TiO2 nanowires and Fe3O4 quantum dot modified carbon nitride are loaded on the surface of the conductive substrate; the mass percentage of the TiO2 nanowires in the catalyst is 85% to 90%; the mass percentage of the Fe3O4 quantum dot modified carbon nitride in the catalyst is 1% to 9%.
[0009] The present invention also discloses a method for preparing the photoelectric-Fenton catalyst as described above, comprising the following steps:
[0010] (1) placing graphite felt in an acidic aqueous solution containing a titanium precursor, reacting at 150° C. to 170° C. for 20 h to 22 h, and cooling and drying to obtain graphite felt with grown TiO2 nanowires;
[0011] (2) dispersing melamine and cyanuric acid in a solvent for reaction, separating a solid product, freeze-drying the solid product to obtain a precursor, and then calcining the precursor to obtain porous carbon nitride;
[0012] (3) dispersing the porous carbon nitride in a solvent, adding FeCl3·6H2O and FeCl2·4H2O, mixing at 80°C to 85°C for 30min to 60min, then adding ammonia water and mixing for 30min to 60min, cooling, washing, and drying in sequence to obtain Fe3O4 / CN;
[0013] (4) Fe3O4 / CN is loaded on the surface of graphite felt on which TiO2 nanowires are grown by electrophoretic deposition, and then cured at 160°C to 180°C for 2h to 4h to obtain the photoelectric-Fenton catalyst.
[0014] Optionally, in step (1), the titanium precursor in the acidic aqueous solution containing the titanium precursor includes one or more of tetrabutyl titanate, concentrated hydrochloric acid, and deionized water.
[0015] Optionally, in step (1), the pH of the acidic aqueous solution containing the titanium precursor is 2 to 4; the concentration of titanium ions in the acidic aqueous solution containing the titanium precursor is 0.02 mol / L to 0.021 mol / L.
[0016] Specifically, the TiO2 obtained in step (1) is a nanowire structure, which has a high diffusion coefficient of photogenerated electrons and photogenerated holes, and the gaps between the wires are conducive to the design of the composite catalyst.
[0017] Optionally, in step (2), the mass ratio of the melamine to the cyanuric acid is 1:(1 to 1.1).
[0018] Optionally, in step (2), the solvent includes one or more of water, melamine and cyanuric acid.
[0019] Optionally, in step (2), the reaction temperature is between 25°C and 30°C, and the reaction time is between 12h and 24h.
[0020] Optionally, in step (2), the calcination includes: heating the temperature to 540°C to 550°C at a heating rate of 2.3°C / min to 2.5°C / min, and then keeping the temperature for 4h to 5h.
[0021] Specifically, the carbon nitride obtained in step (2) has a porous structure, so that the catalyst of the present invention has a larger specific surface area and more reactive sites, and can better undergo redox reactions with pollutants, thereby enhancing degradation efficiency.
[0022] Optionally, in step (3), the solvent is an aqueous solution containing ethanol;
[0023] Optionally, in step (3), the mass volume ratio of FeCl3·6H2O, FeCl2·4H2O and aqueous ammonia is 27 mg:9 mg:1 mL.
[0024] Specifically, in step (3), Fe3O4 is loaded onto the surface of the porous carbon nitride by in-situ deposition and high-temperature drying, and the iron ions are loaded on the surface in the form of chemical bonds.
[0025] Optionally, in step (4), elemental iodine and Fe3O4 / CN are dissolved in acetone to form an electrolyte. In a two-electrode system, a platinum wire is used as an anode and a graphite felt with TiO2 nanowires grown on it is used as a cathode. The two electrodes are immersed in the electrolyte in parallel for electrophoretic deposition. The voltage is 30V to 50V, the deposition time is 15min to 30min, and the cathode is 1cm to 1.5cm away from the anode.
[0026] Specifically, in step (4), by introducing g-C3N4 with a narrow band gap and visible light response, the positions of the conduction band and valence band of the two are matched, and the separation of photogenerated carriers is promoted by forming a heterojunction.
[0027] Optionally, the graphite felt is pretreated before use, including: washing the graphite felt with acetone and ethanol solutions to remove surface impurities, and calcining at 450° C. to 500° C. for 2 h to 3 h after drying to obtain pretreated graphite felt.
[0028] Specifically, the present invention designs an optimal component system, matches the raw material ratio and reaction conditions with the components, so that the crystal phase, surface morphology and activity of the obtained catalyst meet the optimal use requirements, and finally achieves performance optimization.
[0029] The present invention also discloses a photoelectric-Fenton catalyst as described above, or an application of the photoelectric-Fenton catalyst prepared by the preparation method as described above in degrading emerging pollutants.
[0030] Optionally, the emerging pollutants include one or more of tetracycline, norfloxacin, and oxytetracycline.
[0031] Optionally, the application includes the following steps: adding the photoelectric-Fenton catalyst to wastewater containing antibiotic pollutants, performing dark field adsorption for 120 minutes to 180 minutes in the absence of light, and stirring until adsorption equilibrium is reached, turning on the experimental xenon lamp and the adjustable DC regulated voltage power supply, and performing the photoelectric-Fenton reaction for 30 minutes to 180 minutes.
[0032] Optionally, the concentration of the wastewater containing emerging pollutants is 10 mg / L to 40 mg / L, and the pH of the wastewater containing antibiotic pollutants is 2 to 9, with a preferred pH of 3.
[0033] Optionally, the light source used for the photoelectric-Fenton reaction is an experimental xenon lamp, which is filtered with a 420nm filter.
[0034] Implementing the embodiments of the present invention will have the following beneficial effects:
[0035] The photoelectric-Fenton catalyst provided in an embodiment of the present invention is prepared by a hydrothermal method to obtain a graphite felt on which TiO2 nanowires are grown, and then Fe3O4 quantum dots are used to load porous carbon nitride. Finally, Fe3O4 / CN is deposited on the graphite felt on which TiO2 nanowires are grown and dried to obtain a photoelectric-Fenton catalyst having graphite felt as a conductive substrate, Fe3O4 quantum dots-modified carbon nitride and titanium dioxide as a composite. The catalyst has high degradation efficiency, strong universality and excellent stability. The preparation method provided by the present invention is simple, low in cost, high in degradation efficiency and strong in universality, and can be applied to the degradation of emerging pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 These are scanning electron microscope images of Example 1 of the present invention, wherein A is an electron microscope image of TiO2 / GF; and B is an electron microscope image of 5% Fe3O4 / g-C3N4 / TiO2 / GF.
[0037] Figure 2X-ray diffraction (XRD) patterns of g-C3N4, TiO2, TiO2 / GF of the present invention and Fe3O4 / g-C3N4 / TiO2 / GF of Examples 1-5.
[0038] Figure 3 It is the infrared spectrum (FTIR) diagram of TiO2 / GF of the present invention and Fe3O4 / g-C3N4 / TiO2 / GF of Examples 1-5.
[0039] Figure 4 It is the ultraviolet spectrum (UV-vis) diagram of TiO2 / GF of the present invention and Fe3O4 / g-C3N4 / TiO2 / GF of Examples 1-5.
[0040] Figure 5 It is the fluorescence spectrum (PL) diagram of CN, CN / TiO2 / GF of the present invention and Fe3O4 / g-C3N4 / TiO2 / GF of Examples 1-5.
[0041] Figure 6 This is a graph showing the degradation efficiency of tetracycline pollutants by TiO2 / GF of the present invention and Fe3O4 / g-C3N4 / TiO2 / GF of Examples 1-5.
[0042] Figure 7 This is a graph showing the degradation efficiency of 5% Fe3O4 / g-C3N4 / TiO2 / GF of Example 1 of the present invention on different antibiotic pollutants.
[0043] Figure 8 This is a graph showing the degradation efficiency of tetracycline pollutants by 5% Fe3O4 / g-C3N4 / TiO2 / GF at different pH values in Example 1 of the present invention.
[0044] Fig. 9 This is a test chart of the degradation stability of tetracycline pollutants by 5% Fe3O4 / g-C3N4 / TiO2 / GF in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0046] Example 1
[0047] The preparation method of the photoelectric-Fenton catalyst of this embodiment comprises the following steps:
[0048] (1) The graphite felt was cut into small pieces of 2 cm × 3 cm, cleaned with acetone and ethanol solution to remove surface impurities, dried in an electric blast drying oven at 80 ° C, and finally placed in a muffle furnace at 450 ° C for 2 h for heat treatment.
[0049] (2) Under magnetic stirring, 10 mL of concentrated hydrochloric acid was added to the inner lining of a reactor containing 10 mL of deionized water, and then 0.25 mL of tetrabutyl titanate was slowly added and stirred until the solution was transparent. The graphite felt pretreated in step (1) was placed downward at an angle of 30° to the inner lining and reacted in a polytetrafluoroethylene high-pressure reactor at 150° C. for 20 h. After cooling and drying, a graphite felt TiO2 / GF with grown TiO2 nanowires was obtained.
[0050] (3) 1.2612 g of melamine and 1.2907 g of cyanuric acid were dissolved in 60 ml of deionized water and stirred for 12 h. The material was freeze-dried and the dried sample was calcined in a muffle furnace at 550 °C for 4 h with a temperature gradient of 2.3 °C / min to obtain porous g-C3N4.
[0051] (4) 0.4389 g of porous g-C3N4 was dispersed in ethanol / water (2:1) and ultrasonicated for 30 min to obtain a suspension. Then, 0.0541 g of FeCl3·6H2O and 0.0199 g of FeCl2·4H2O were added to the suspension, and the mixture was stirred at 80 °C for 30 min. Subsequently, 2 mL of ammonia water was quickly injected into the reactant and stirred for another 30 min. After cooling, the reactant was washed several times with deionized water and ethanol and dried to obtain Fe3O4 / CN.
[0052] (5) 20 mg of elemental iodine and 10 mg of Fe3O4 / CN were dissolved in 30 mL of acetone and ultrasonicated for 15 min. In a two-electrode system, a platinum wire was used as the anode and TiO2 / GF was used as the cathode. The two electrodes were immersed in the electrolyte in parallel (about 1.5 cm apart) and a voltage of 50 V was applied for electrophoretic deposition for 15 min to obtain 5% Fe3O4 / g-C3N4 / TiO2 / GF, which was then cured at 160°C to 180°C for 2h to 4h.
[0053] The 5% Fe3O4 / g-C3N4 / TiO2 / GF composite material prepared above was tested by scanning electron microscopy. Figure 1 As shown, it can be seen that the original morphology and nanowire structure of TiO2 are maintained.
[0054] Embodiment 2-5
[0055] The difference between Examples 2-5 and Example 1 is that the amount of porous g-C3N4 added in step (4) is changed. Except for the above differences, other operations are the same and will not be repeated here. The amounts of porous g-C3N4 added in Examples 2-5 are 2.2869g, 0.7469g, 0.3069g, and 0.2336g, respectively. According to the preparation method of Example 1, 1% Fe3O4 / g-C3N4 / TiO2 / GF, 3% Fe3O4 / g-C3N4 / TiO2 / GF, 7% Fe3O4 / g-C3N4 / TiO2 / GF, and 9% Fe3O4 / g-C3N4 / TiO2 / GF were prepared respectively. It was found that the scanning electron microscopy results of 1%Fe3O4 / g-C3N4 / TiO2 / GF, 3%Fe3O4 / g-C3N4 / TiO2 / GF, 7%Fe3O4 / g-C3N4 / TiO2 / GF, and 9%Fe3O4 / g-C3N4 / TiO2 / GF were similar to those of 5%Fe3O4 / g-C3N4 / TiO2 / GF. At the same time, the X-ray diffraction (XRD), infrared spectroscopy (FTIR), ultraviolet spectroscopy (UV-vis), and fluorescence spectroscopy (PL) of 1%Fe3O4 / g-C3N4 / TiO2 / GF, 3%Fe3O4 / g-C3N4 / TiO2 / GF, 7%Fe3O4 / g-C3N4 / TiO2 / GF, and 9%Fe3O4 / g-C3N4 / TiO2 / GF showed similar results. Figure 2-5 shown.
[0056] Example 6
[0057] The application effect of Fe3O4 / g-C3N4 / TiO2 / GF prepared in Examples 1-5 in the degradation of tetracycline wastewater was analyzed as follows:
[0058] (1) Prepare 100 mL of a tetracycline solution with a concentration of 10 mg / L, add the FCNT / GF prepared in Examples 1-5 to the tetracycline solution, and place the solution in a reaction apparatus.
[0059] (2) Dark field adsorption was performed under lightless conditions to achieve adsorption equilibrium. The dark field adsorption time was 120 min. After the dark field adsorption was completed, the experimental xenon lamp and external bias were turned on, and the ultraviolet light was removed with a 420 nm filter. The reaction was continued with stirring for 180 min. A sample was drawn every 30 min, with a draw volume of 2 mL. The sample was centrifuged and the supernatant was measured for its absorbance in an ultraviolet spectrophotometer. The degradation rate of tetracycline was calculated using formula (1). The degradation results are shown in Figure 6 shown.
[0060] X=(C0-C) / C0×100% (1)
[0061] Wherein, X is the degradation rate of tetracycline, C0 is the initial concentration of tetracycline (mol / L), and C is the concentration of tetracycline after degradation (mol / L).
[0062] Example 7
[0063] The application effect of 5% Fe3O4 / g-C3N4 / TiO2 / GF prepared in Example 1 in the degradation of tetracycline wastewater with different concentrations was analyzed as follows:
[0064] (1) 100 mL of tetracycline solutions with concentrations of 10 mg / L, 20 mg / L, and 40 mg / L were prepared respectively, and the pH values thereof were adjusted. The 5% FCNT / GF prepared in Example 1 was added to the above solutions, and the solutions were placed in a reaction apparatus.
[0065] (2) Dark field adsorption was performed under lightless conditions to achieve adsorption equilibrium. The dark field adsorption time was 120 min. After the dark field adsorption was completed, the experimental xenon lamp and external bias were turned on, and the ultraviolet light was removed with a 420 nm filter. The reaction was continued with stirring for 180 min. A sample was drawn every 30 min, with a draw volume of 2 mL. The sample was centrifuged and the supernatant was measured for its absorbance in an ultraviolet spectrophotometer. The degradation rate of tetracycline was calculated using formula (1). The degradation results are shown in Figure 7 shown.
[0066] Example 8
[0067] The application effect of 5% Fe3O4 / g-C3N4 / TiO2 / GF prepared in Example 1 in the degradation of tetracycline wastewater at different pH values was analyzed as follows:
[0068] (1) Prepare 100 mL of tetracycline solutions with a concentration of 10 mg / L and pH values of 1, 3, 5, 7, and 9, respectively. Adjust the tetracycline solutions to different pH values, then add the catalysts to the tetracycline solutions in sequence and place them in a reaction apparatus.
[0069] (2) Dark field adsorption was performed under lightless conditions to achieve adsorption equilibrium. The dark field adsorption time was 120 min. After the dark field adsorption was completed, the experimental xenon lamp and external bias were turned on, and the ultraviolet light was removed with a 420 nm filter. The reaction was continued with stirring for 180 min. A sample was drawn every 30 min, with a draw volume of 2 mL. The sample was centrifuged and the supernatant was measured for its absorbance in an ultraviolet spectrophotometer. The degradation rate of tetracycline was calculated using formula (1). The degradation results are shown in Figure 8 shown.
[0070] Example 9
[0071] After the degradation experiment, the 5% Fe3O4 / g-C3N4 / TiO2 / GF photoanode was washed with ethanol and deionized water, and then dried at 80℃ for 12h. The cycle test experiment was carried out. The results are shown in Fig. 9 shown.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A photoelectric-Fenton catalyst, characterized in that: The catalyst consists of a conductive substrate, TiO2 nanowires and Fe3O4 quantum dot-modified carbon nitride; Wherein, the conductive substrate is graphite felt, and the TiO2 nanowires and Fe3O4 quantum dot-modified carbon nitride are loaded on the surface of the conductive substrate; The mass percentage of the TiO2 nanowires in the catalyst is 85% to 90%; the mass percentage of the Fe3O4 quantum dot-modified carbon nitride in the catalyst is 1% to 9%.
2. A method for preparing the photoelectric-Fenton catalyst according to claim 1, characterized in that: The following steps are involved: (1) placing graphite felt in an acidic aqueous solution containing a titanium precursor, reacting at 150° C. to 170° C. for 20 h to 22 h, and cooling and drying to obtain a graphite felt on which TiO2 nanowires are grown; (2) dispersing melamine and cyanuric acid in a solvent for reaction, separating a solid product, freeze-drying the solid product to obtain a precursor, and then calcining the precursor to obtain porous carbon nitride; (3) dispersing the porous carbon nitride in a solvent, adding FeCl3·6H2O and FeCl2·4H2O, mixing at 80°C to 85°C for 30min to 60min, then adding ammonia water and mixing for 30min to 60min, cooling, washing, and drying in sequence to obtain Fe3O4 / CN; (4) Fe3O4 / CN is loaded on the surface of graphite felt on which TiO2 nanowires are grown by electrophoretic deposition, and then cured at 160°C to 180°C for 2h to 4h to obtain the photoelectric-Fenton catalyst.
3. The preparation method according to claim 2, characterized in that: In step (1), the titanium precursor in the acidic aqueous solution containing the titanium precursor includes one or more of tetrabutyl titanate, concentrated hydrochloric acid, and deionized water; The pH of the acidic aqueous solution containing the titanium precursor is 2 to 4; The concentration of titanium ions in the acidic aqueous solution containing the titanium precursor is 0.02 mol / L to 0.021 mol / L.
4. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of the melamine to the cyanuric acid is 1:(1-1.1); The solvent includes one or more of water, melamine and cyanuric acid; The reaction temperature is between 25°C and 30°C, and the reaction time is between 12h and 24h; The calcination comprises: heating the temperature to 540° C. to 550° C. at a heating rate of 2.3° C. / min to 2.5° C. / min, and then keeping the temperature for 4 h to 5 h.
5. The preparation method according to claim 2, characterized in that: In step (3), the solvent is an aqueous solution containing ethanol.
6. The preparation method according to claim 2, characterized in that: In step (4), elemental iodine and Fe3O4 / CN are dissolved in acetone to form an electrolyte. In a double-electrode system, a platinum wire is used as an anode and a graphite felt with TiO2 nanowires grown thereon is used as a cathode. The two electrodes are immersed in the electrolyte in parallel for electrophoretic deposition. The voltage is 30V to 50V, the deposition time is 15min to 30min, and the cathode is 1cm to 1.5cm away from the anode.
7. The preparation method according to claim 2, characterized in that: The graphite felt is pretreated before use, including: The graphite felt is cleaned with acetone and ethanol solution to remove surface impurities, dried, and then calcined at 450° C. to 500° C. for 2 h to 3 h to obtain pretreated graphite felt.
8. Use of the photoelectric-Fenton catalyst as claimed in claim 1, or the photoelectric-Fenton catalyst prepared by the preparation method as claimed in any one of claims 2 to 7 in the degradation of emerging pollutants.
9. The use according to claim 8, characterized in that: The emerging pollutants include one or more of tetracycline, norfloxacin and oxytetracycline.
10. The use according to claim 8, characterized in that: The application comprises the following steps: The photoelectric-Fenton catalyst is added to the wastewater containing antibiotic pollutants, and dark field adsorption is performed for 120 minutes to 180 minutes under lightless conditions, and stirring is performed until adsorption equilibrium is reached, and then the experimental xenon lamp and the adjustable DC regulated voltage power supply are turned on to perform the photoelectric-Fenton reaction for 30 minutes to 180 minutes; Wherein, the concentration of the wastewater containing emerging pollutants is 10mg / L to 40mg / L, and the pH of the wastewater containing antibiotic pollutants is 2 to 9; The light source used for the photoelectric-Fenton reaction is an experimental xenon lamp, which is filtered with a 420nm filter.